2010
DOI: 10.1016/j.jinf.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A novel screening method for influenza patients using a newly developed non-contact screening system

Abstract: The proposed system appears promising for application in accurate screening for influenza patients at places of mass gathering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 14 publications
1
60
0
Order By: Relevance
“…Infrared thermal imaging is mentioned as an appropriate technique for mass screening of fever [1]. The temperature of the inner canthus of the eye (T ca ) seems the most suited spot [2] although others argue that the average temperature of the face may be valuable as well, albeit in combination with other physiological parameters [3]. A recent review observed a wide range in fever detection sensitivity from 4 to 90%, while specificity ranged from 75 to almost 100% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Infrared thermal imaging is mentioned as an appropriate technique for mass screening of fever [1]. The temperature of the inner canthus of the eye (T ca ) seems the most suited spot [2] although others argue that the average temperature of the face may be valuable as well, albeit in combination with other physiological parameters [3]. A recent review observed a wide range in fever detection sensitivity from 4 to 90%, while specificity ranged from 75 to almost 100% [4].…”
Section: Introductionmentioning
confidence: 99%
“…This makes the technique favorable for epidemiological surveillance and massmedicine. In fact, we have already attempted to apply this technique for screening of individuals with suspected infection at a quarantine depot (Matsui et al, , 2010. We have already succeeded in diagnosing influenza patients in as little as 10 s per person.…”
Section: Resultsmentioning
confidence: 99%
“…This system enables medical inspection by measuring heart and respiratory rates, as well as body temperature by infrared thermography (Matsui et al, , 2010. A similar system is already being tested at the quarantine station at Naha Airport for domestic flights and at Narita International Airport in Tokyo.…”
Section: Screening and Medical Examination Of Influenza Patientsmentioning
confidence: 99%